A retrospective study on predictive risk of infection complication post percutaneous nephrolithotomy in Hospital Universiti Sains Malaysia from 2013 to 2018 - Ismail, Razif (2021)
Background: Percutaneous nephrolithotomy (PCNL) has become a standard procedure in a large, complex stone of the upper urinary tract since it was introduced into the endourologist’s armamentarium 4 decades back. Though the procedure is safe, complication still occur and are well reported in literature. This study aims to investigate the pre- and intraoperative predictors on infective complication in patient undergoing PCNL in Hospital Universiti Sains Malaysia. Methodology: This is a retrospective cohort study in a single institution involving patients undergoing PCNL between 2013 and 2018 in a teaching hospital at East Coast Malaysia. The variables were categorized into preoperative risk factors and intraoperative risk factors and the outcomes measured include infection complications of fever, systemic inflammatory response syndrome (SIRS) and sepsis. Multiple logistic regression analysis was used to determine independent risk factor associated with infective complication. Data were analysed using SPSS version 26. Result: We identified 86 consecutive patients who underwent primary PCNL that fulfil the inclusion criteria. The prevalence of infective complications was 31.4% (95% CI = 21.8,42.3), SIRS 17 patients (n=19.8%) and sepsis 6 patients (n=7%). There was no significant association between age, present of comorbidities, ethnicity, present of hydronephrosis and duration of surgery with the occurrence of infective complications. Those with infective complications were more likely to be associated with choice of